Analisis Penerapan SAK-ETAP (Standar Akuntansi Keuangan Entitas Tanpa Akuntabilitas Publik) pada Penyajian Laporan Keuangan Koperasi Pegawai Republik Indonesia (KPRI) “Manfaat” LPMP Jawa Tengah - Mudjiyono, Mudjiyono (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Institut Teknologi dan Bisnis (ITB) Semarang, 2020)
This study aims to find and test the rules of the Entity without Public Accountability (SAK-ETAP) Financial Accounting Standards set by the Indonesian Institute of Accountants (IAI) and which is enacted in the regulation of the Minister of Cooperatives and Small and Medium Enterprises of the Republic of Indonesia No. 12/per/M.KUKM/IX/2015 concerning Cooperative Accounting Guidelines that are applied factually to KPRI